Proactive Personality as a Critical Condition for Seeking Advice and Crafting Tasks in Ambiguous Roles - Inyong Shin; Minwoo Kim (Behavioral Sciences, 2022)
In increasingly ambiguous work contexts, advice-seeking and task crafting behaviors are becoming more significant than ever before. Drawing on the uncertainty reduction theory, this study examined how role ambiguity would affect advice-seeking and task crafting. We also investigated whether a proactive personality would moderate the effects based on the capacity–willingness–opportunity model. The results, based on a two-wave design with a sample of 160 employees in South Korea, revealed that role ambiguity did not affect advice-seeking and task crafting directly. However, it was found that, as role ambiguity increased, employees with proactive personality became more involved in advice-seeking and task crafting. These findings indicate that role ambiguity serves as an opportunity for proactive employees who have the capacity and willingness to seek advice and craft tasks.